Narrative and Design for Wellbeing: A User-Centered Approach - Jordan, Patrick W.; Bardill, Andy; Herd, Kate; Grimaldi, Silvia (ACTIO Journal of technology in design, film arts and visual communication, 2020)
The narratives that we have about our lives can affect our wellbeing. The Products and services that we own or use can play a role in these narratives (Jordan, Bardill, Herd and Grimaldi, 2020) – the car that says "I am a success", the toy that says "I am a good parent" or the customer-care that lets me know that "I am not important.” In an exploratory study, 41 undergraduate students described experiences with two different products or services – one that enabled and one that failed to enable a desired narrative. These 82 case studies were analysed to explore concepts relevant to narrative in the context of product and service use. We identify six different ways in which a product or service can enable a narrative, evaluate Jung’s archetypes as a means of narrative classification, and explore the roles of products and users in enabling stories. The implications for user research and design are explored.